Photographier les X-codes de La Nouvelle-Orléans après Katrina. Perspectives mémorielles d’une exposition sur le Web - Maude Oswald (IdeAs)
New Orleans, 2005. The X-codes, cross-shaped forms sprayed on houses by search and rescue teams emerged in the chaos following Katrina. The repetition of the Xs on the walls of nearly every house, as well as their visual strength and symbolic meanings rapidly turned them into icons of the catastrophe. Confronted with powerful symbols embodying the destruction of the city and the disruption of personal lives, New Orleans residents chose to preserve, erase or modify them. Photographers then began to represent these visually compelling testimonial marks, as well as record traces of signs often bound to disappear over time. In doing so, they participated in building a memory of the disaster. The collective exhibition Katrina+5: An X-Code Exhibition, put online in 2010 to commemorate the fifth anniversary of the catastrophe, helps us to understand the memorial potentialities of the X-codes, from their actual presence on houses to their photographs and beyond in the changing space of the Web.